الآيات القرآنية الصريحة في ختم النبوة (دراسة دلالية): The Explicit Qur’anic Verses on the Finality of Prophethood (A Semantic Study) - Rahat (Al-Amīr Research Journal for Islamic Studies, 2025)
The issue of the finality of Prophethood is important because Muslims believe that the Prophet Muhammad (PBUH) is the final prophet of Allah. And the Prophet (peace be upon him) was sent to every nation and every human class, and the book brought by him, the Quran, abrogates the commands of all heavenly books and is comprehensive and preventive in all matters of future laws and regulations. The Prophet (peace and blessings of Allah be upon him) has been sent as a messenger to every nation and every human class on the face of the earth, and the book he brought is the Qur’an, which abrogates the rulings of all the heavenly books and in the rulings and laws of all matters for the future. It is comprehensive. In the same book, Allah said: (Muhammad is not the father of any of your men, but He is the Messenger of Allah and the Seal of the Prophets. And Allah is All-Knower of everything.) Similarly, there are various hadiths from the Messenger of Allah (peace be upon him) on this subject, which indicate that He is the last messenger of Allah. There are many verses in the Holy Qur’an that support and confirm the belief of the finality of Prophethood. There is no doubt that the entire Quran is proof of the finality of Prophethood, but there are some verses that specifically determine the finality of Prophethood. Some verses are explicit and some are implicit. In this article, I have collected the verses indicating Prophethood and provided their interpretations based on syntactic and semantic levels, and it has also been mentioned how much emphasis is there in these verses. We pray to Allah to keep the benefit of this article forever and make it purely for His honor. May blessings and peace upon our master Muhammad and his family and companions, and those who follow him with goodness until the Day of Resurrection. Key words: Seal of prophet hood, Specific Verses, Semantic Study